FUTURE OF LANDSCAPE PLANNING AS THE MEANS FOR OPTIMIZATION OF AGROECO-SYSTEMS FUNCTIONING - Максименко, Н. В.; Порохняк, О. В. (Man and Environment. Issues of Neoecology, 1970)
It was determined that landscape planning as a means for optimizing the functioning of agricultural ecosystems has significant potential. The results of the inventory phase of landscape planning of Korobochkinskaya agricultural company were given as an example of updating the classic concept. There were shown the problems of adaptation of landscape planning under the framework research objectives of agro-ecosystems. It was found that relief and soil are the main landscape elements that need to be explored in the framework of a particular objective.